Reliability of the Spin-T Cervical Goniometer in Measuring Cervical Range of Motion in an Asymptomatic Indian Population - Agarwal, S.; Allison, Garry; Singer, K. (Elsevier Inc, 2005)
Objective. To examine the intratester reliability of the Spin-T goniometer, a cervical range of motion device, in a normal Indian population. Methods. Subjects comprised 30 healthy adults with mean age of 34 years (range, 18-65 years). The subjects were stabilized in the sitting position and the Spin-T goniometer mounted on the head of the subject. The study design was a within-subject repeated intratester reliability trial conducted for cervical range of motion in 6 directions of movement. Three measurements were taken in each direction (flexion, extension lateral flexion, and lateral rotation) per participant. Reliability coefficients, intraclass correlation coefficients, and 95% confidence interval were derived from repeated-measures analysis of variance (ANOVA). Where differences in ANOVA were detected, a paired t test was conducted and the typical error values and coefficient of variance were calculated. Results. All repeated measures showed high intraclass correlation coefficients (all >0.96, P <.01). The ANOVA detected no differences between trials for all movements except rotation. The typical error values for the rotation trials did not exceed 2.5 and the coefficient of variance did not exceed 4%, which is clinically acceptable considering the normally variable cervical range of movement. Conclusion. In this study, the Spin-T goniometer proved to be a reliable measuring instrument for cervical range of movement in an Indian population. The use of a laser pointer fixed to the instrument ensured a consistent neutral start position.